KESALEHAN SOSIAL TOKOH UTAMA DALAM CERPEN RUMAH YANG TERANG KARYA AHMAD TOHARI - nunzilah, luluk; Ari Ambarwati (Universitas Islam Malang, 2024)
This research employs a descriptive-analytical qualitative approach to explain how the main character in the short story demonstrates social piety through their attitudes, actions, and interactions with other characters in the narrative. Social piety is a manifestation of religious teachings in social life, encompassing honesty, justice, and concern for others. This study aims to provide a deeper understanding of the relationship between the main character's social piety and the overall theme of the story, as well as the values the author wishes to convey. This analysis offers greater insights into the moral messages or values the author seeks to communicate through their work.